Extracorporeal CO2 removal in acute exacerbation of COPD unresponsive to non-invasive ventilation - Vincent Ioos; Daniel Silva; Mathilde Azzi; Jerome Aboab; Sophie Alviset; Daria Ushmorova; Luis Ferreira; Nathalie Memain; Tazime Issoufaly; Mathilde Lermuzeaux; Laurent Laine; Rita Serbouti (BMJ Open Respiratory Research)
Background The gold-standard treatment for acute exacerbation of chronic obstructive pulmonary disease (ae-COPD) is non-invasive ventilation (NIV). However, NIV failures may be observed, and invasive mechanical ventilation (IMV) is required. Extracorporeal CO₂ removal (ECCO₂R) devices can be an alternative to intubation. The aim of the study was to assess ECCO₂R effectiveness and safety.Methods Patients with consecutive ae-COPD who experienced NIV failure were retrospectively assessed over two periods of time: before and after ECCO₂R device implementation in our ICU in 2015 (Xenios AG).Results Both groups (ECCO₂R: n=26, control group: n=25) were comparable at baseline, except for BMI, which was significantly higher in the ECCO₂R group (30 kg/m² vs 25 kg/m²). pH and PaCO₂ significantly improved in both groups. The mean time on ECCO₂R was 5.4 days versus 27 days for IMV in the control group. Four patients required IMV in the ECCO₂R group, of whom three received IMV after ECCO₂R weaning. Seven major bleeding events were observed with ECCO₂R, but only three led to premature discontinuation of ECCO₂R. Eight cases of ventilator-associated pneumonia were observed in the control group. Mean time spent in the ICU and mean hospital stay in the ECCO₂R and control groups were, respectively, 18 vs 30 days, 29 vs 49 days, and the 90-day mortality rates were 15% vs 28%.Conclusions ECCO₂R was associated with significant improvement of pH and PaCO₂ in patients with ae-COPD failing NIV therapy. It also led to avoiding intubation in 85% of cases, with low complication rates.Trial registration number ClinicalTrials.gov, NCT04882410. Date of registration 12 May 2021, retrospectively registered.https://www.clinicaltrials.gov/ct2/show/NCT04882410.